Business Failure Pathways: Environmental Stress and Organizational Response - MOULTON, Wilbur N. (Institutional Knowledge at Singapore Management University, 1996)
This paper compares the failure of 73 firms that declared bankruptcy from 1980 to 1986 with the behavior of 73 matching firms that had not failed over the same period. We contrast the relative importance of environmental stress, measured by industry growth/decline, with organizational response, measured by asset and debt growth/decline. Firm effects dominate industry effects in explaining failure. Four distinctive business failure pathways based on firm and industry growth patterns are described. In particular, we conclude that debt-funded, forced-growth strategies create a high risk of failure regardless of industry growth rate.